Thrombosis among 1537 patients with JAK2V617F‐mutated myeloproliferative neoplasms: Risk factors and development of a predictive model. (28th January 2020) - Zhang, Yuhui; Zhou, Yuan; Wang, Yingshao; Teng, Guangshuai; Li, Dapeng; Wang, Yan; Du, Chenxiao; Chen, Yafang; Zhang, Huiqin; Li, Yanqi; Fu, Lixia; Chen, Kangyin; et al.
Abstract: To explore the risk factors of thrombosis in patients with JAK2 V617F ‐ mutated myeloproliferative neoplasms (MPNs), a cohort of 1537 Chinese patients with JAK2 V617F ‐mutated MPN was retrospectively analyzed. The Kaplan‐Meier method and multivariate Cox analysis were used to study the risk factors of thrombosis in patients with JAK2 V617F ‐mutated MPN. Among the 1537 MPN patients, 931, 468, and 138 had polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF), respectively. The median follow‐up time was 7 years (range 1‐47), and 12.8% of patients (197/1537) died during this period. A total of 16.8% (259/1399) of PV and ET patients had secondary myelofibrosis, and 2.5% (38/1537) of patients developed acute myeloid leukemia (AML). Thrombotic events occurred in 43.9% (675/1537) of patients, among which 91.4% (617/675) were arterial thrombosis and 16.6% (112/675) were venous thrombosis. The number of thrombotic events in PV, ET, and PMF patients was 439 (47.2%), 197 (42.1%) and 39 (28.2%), respectively. The multivariate analysis indicated that age ≥60 years old, HCT ≥48%, at least one cardiovascular risk factor, a history of thrombosis, and JAK2 V617F allele burden ( V617F %) ≥50% are risk factors for thrombosis in JAK2 V617F ‐mutated MPN. According to the results of the multivariate analysis, a risk model of thrombosis was established and comprised low‐risk (0 points), intermediate‐risk (1 points) and high‐risk (≥2 points) groups, among which the incidence of thrombosis was 9.1%, 33.7% and 72.9%. For elderly patients with JAK2 V617F ‐mutated MPN and a history of thrombosis, reducing the V617F%, controlling HCT and preventing cardiovascular risk factors are necessary measures to prevent thrombosis. Abstract : We analyzed the clinical characteristics, laboratory characteristics, cytogenetics, thromboembolism status, disease progression, and overall survival of 1537 Chinese MPN patients with the JAK2 V617F mutation. The multivariate analysis indicated that age ≥60 years old, HCT ≥48%, at least one cardiovascular risk factor, history of thrombosis, and JAK2 V617F allele burden ( V617F %) ≥50% are risk factors for thrombosis of JAK2 V617F ‐mutated MPN. Our study suggested that for elderly patients with JAK2 V617F ‐mutated MPN and a history of thrombosis, reducing V617F %, controlling HCT, and mitigating cardiovascular risk factors are necessary measures to prevent thrombosis.